American cosmic : UFOs, religions, technology - Pasulka, Diana Walsh (Oxford University Press, 2019)
"More than half of American adults and more than seventy-five percent of young Americans believe in intelligent extraterrestrial life. This level of belief rivals that of belief in God. In American Cosmic, D.W. Pasulka examines the mechanisms that foster a thriving belief in extraterrestrial life. Her work takes her from Silicon Valley to the Vatican Secret Archive and reveals how media has supplanted religion as a cultural authority that offers believers answers about non-human intelligent life"--